The 30 Juz Al-Qur'an Memorization Program as a Competitive Advantage for Madrasahs : Program Hafalan Al-Qur'an 30 Juz sebagai Keunggulan Kompetitif Madrasah - Sucipto, Hadi; Haryanto, Budi (Adabiyah: Jurnal Pendidikan Islam, 2025)
General background: The rapid growth of educational institutions has led to increasing competition, pushing schools to develop unique competitive strategies to attract students. Specific background: MA Islam Terpadu Darul Fikri (DAFI) in Sidoarjo leverages a 30-juz Quran memorization program to gain a competitive advantage. Knowledge gap: While many institutions use competitive strategies, there is a lack of specific research detailing how a comprehensive Islamic memorization program, integrated with general education, is successfully implemented as a core institutional strategy. Aims: This study investigates how the 30-juz Quran memorization program functions as a competitive advantage for MA DAFI. Results: The findings indicate that MA DAFI effectively integrates general education, religious studies, and skills training under a "one for all" concept. The success of this program is supported by internal factors, such as professional management, and external factors, including government policies and technological changes. Novelty: This research provides a detailed case study demonstrating how an integrated Quran memorization program can be a successful and sustainable competitive strategy for an Islamic school. Implications: The findings offer a model for other Islamic educational institutions seeking to build a unique market position and meet the needs of parents who want formal education combined with religious memorization. Highlights : The 30-juz Quran memorization program is MA DAFI's main competitive advantage. The institution integrates general education, religious studies, and skills training. The school's success is supported by professional management and adaptability to external factors. Keywords: Quran, Program, Al-Qur'an, Competitive Advantage, Islamic Education